2000
DOI: 10.1002/1097-4644(20001201)79:3<486::aid-jcb130>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

LINE L1 retrotransposable element is targeted during the initial stages of apoptotic DNA fragmentation

Abstract: Using a directional cloning strategy, DNA sequence information was obtained corresponding to the site of early radiation-induced apoptotic DNA fragmentation within the human lymphoblastoid cell line TK6. Data were obtained from 88 distinct clones comprising approximately 65 kbp of sequenced material. Analysis of all cloned material showed that sequences in the 10 bp immediately adjacent to the cleavage sites were enriched in short oligoT tracts. The proportion of repetitive DNA within the entire cloned materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The size distribution of DNA fragments derived from normal and apoptotic cells may be strikingly similar depending on the extent of the proteolytic treatment, in line with the fact that DNA fragmentation in the caspase‐dominated milieu of apoptotic cells is already observed at mild proteolytic circumstances [Szabó, 1995]. Although the ∼50 kb fragments were shown to include blunt‐ended molecules [Khodarev et al, 2000], their proportion in the cell lysates was not investigated. Furthermore, the biochemistry of the cleavages is probably complex (see Wu et al, 2000, above; Jin et al, 1999), therefore, the blunt [Khodarev et al, 2000] or 1‐base 5′‐ overhangs with 5′‐phosphate and 3′‐hydroxyl [Widlak et al, 2000] end configuration reported for apoptotic fragmentation should not be considered decisive evidence against the relationship between the two phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size distribution of DNA fragments derived from normal and apoptotic cells may be strikingly similar depending on the extent of the proteolytic treatment, in line with the fact that DNA fragmentation in the caspase‐dominated milieu of apoptotic cells is already observed at mild proteolytic circumstances [Szabó, 1995]. Although the ∼50 kb fragments were shown to include blunt‐ended molecules [Khodarev et al, 2000], their proportion in the cell lysates was not investigated. Furthermore, the biochemistry of the cleavages is probably complex (see Wu et al, 2000, above; Jin et al, 1999), therefore, the blunt [Khodarev et al, 2000] or 1‐base 5′‐ overhangs with 5′‐phosphate and 3′‐hydroxyl [Widlak et al, 2000] end configuration reported for apoptotic fragmentation should not be considered decisive evidence against the relationship between the two phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of these predilection points might be useful for understanding how apoptotic DNA fragmentation is superimposed on analogous phenomena observed in non‐apoptotic cells. Certain aspects of chromatin structure may also be reflected by the phenomenon studied, in view of the fact that loop‐size fragmentation accompanying apoptosis is thought to reflect the loop‐level of higher‐order chromatin organization [Razin et al, 1991; Oberhammer et al, 1993; Gromova et al, 1995; Lagarkova et al, 1995; Khodarev et al, 2000]. Furthermore, molecular analysis of the breakpoints involved in ∼50 kb fragmentation could perhaps open up leads to the possible relationship between these fragile sites and the hot‐spots of pathological gene rearrangements.…”
mentioning
confidence: 99%